Integrating social responsibility in human resource practices in Makkah Al- Mukarramah hotels - Alkhadidi, Abdulelah Eidhah (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aims to Knowing the reality of applying the practice of social responsibility in human resources in Makkah Al- Mukarramah hotels. To achieve the aims of the study the researcher used the descriptive and analytical approach, and the study population was represented in all five- star hotels in Makkah, which numbered (51), where the comprehensive inventory method was followed and the managers of the human resources department in those hotels were chosen to answer the questionnaire. The findings of the statistical analysis showed Makkah Al- Mukarramah hotels practice social responsibility, the results showed a high dgree in Makkah hotels towards practices of social responsibility the human resource management policies. The study has recommended Inclusion of social responsibility within the practices of human resources in Makkah Al- Mukarramah hotels, as well as within its principles, The necessity for hotels to diversify the programs related to their social responsibility towards their human resources, to develop them permanently and to innovate in them to improve the performance of the hotel as a whole.